Extended environmental Kuznets curve in Asia-Pacific countries: an empirical analysis - Nguyen Binh Duong; Everett E. Mayers; Nguyen Duc Nhan; Dau Thu Huong; Hoang Thi Thuy Duong (Journal of International Economics and Management, 2022)
The effects of climate change are being recognized in all regions of the world and they are predicted to increase in the coming decades. This paper aims to study the impacts of economic growth, energy use, and trade liberalization on CO2 emissions in Asia-Pacific countries. By using panel data to build an Environmental Kuznet Curve (EKC), the empirical result shows that the EKC of Asia-Pacific countries has N-shape. Besides, the energy use is one of the factors that worsen the environment. Finally, trade liberalization is an important factor that improves environmental quality in the region.